Faktor-Faktor yang Mempengaruhi Kinerja Pengawas Koperasi Serba Usaha - Gunawan, I Kadek Ardi; Badera, I Dewa Nyoman (E-Jurnal Akuntansi, 2019)
Supervisors are people who are appointed and given the responsibility to control activities within an organization. Cooperative supervisors are part of members who have an obligation to oversee all operations carried out by the cooperative. This study aims to obtain empirical evidence related to the influence of independence, professional expertise, work experience, level of education, and training programs on the performance of all business cooperative supervisors. The population uses all business cooperatives in Klungkung Regency, with the method of determining the sample, which is a non-probability sampling, especially saturated sampling which uses all members of the population as a sample of 87 people. Research shows that all variables have a positive and significant influence on supervisor performance. Keywords : Independency, Expertise, Experience, Education, Trainin.